(untitled) (Universal International Scientific Journal, 2026)
This article reveals the role of legal education in the formation of legal awareness and legal culture in the minds of the younger generation. It analyzes effective methods and tools for the formation of students’ respect for laws, legal responsibility, civic activity. In addition, the importance of educating a strong legal consciousness and cultured generation serving to build a legal state and civil society through the proper organization of legal education in the educational process is substantiated.